2009
DOI: 10.1002/biot.200800310
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of bacterial blight resistance into Triguna, a high yielding, mid‐early duration rice variety

Abstract: Bacterial blight (BB) is a serious disease of rice in India. We have used molecular marker-assisted selection in a backcross breeding program to introgress three genes (Xa21, xa13, and xa5) for BB resistance into Triguna, a mid-early duration, high yielding rice variety that is susceptible to BB. At each generation in the backcross program, molecular markers were used to select plants possessing these resistance genes and to select plants that have maximum contribution from the Triguna genome. A selected BC3F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 16 publications
5
72
0
Order By: Relevance
“…background selection on carrier chromosome or recombinant selection, background selection on the whole genome [8,46,47], and background selection with trait of interest [48]. The presence of target trait genes must be confirmed by phenotyping in the resulting cross generation mostly at the individual level, and individual phenotypic performance is a good indicator of the genotype only if genes play a major effect on phenotypic performance, and the error of phenotyping is minimal [49].…”
Section: Markersmentioning
confidence: 99%
“…background selection on carrier chromosome or recombinant selection, background selection on the whole genome [8,46,47], and background selection with trait of interest [48]. The presence of target trait genes must be confirmed by phenotyping in the resulting cross generation mostly at the individual level, and individual phenotypic performance is a good indicator of the genotype only if genes play a major effect on phenotypic performance, and the error of phenotyping is minimal [49].…”
Section: Markersmentioning
confidence: 99%
“…Sundaram et al (2008) evaluated four 3-gene pyramided (xa5 + xa13 + Xa21) lines of Samba Mahsuri under AICRIP (All India Coordinated Rice Improvement Project) trials at different hot spot locations and reported a high degree of resistance of the gene pyramided lines indicating broad spectrum resistance conferred by combination of three BB resistance genes. Sundaram et al (2009) again showed that NILs possessing a combination of xa13 and Xa21 in the background of rice variety, Triguna showed high level of resistance to Xoo. Combination of BB resistance genes, xa13 and Xa21 in the background of popular basmati rice variety, Pusa Basmati 1 provided broad-spectrum resistance to BB (Joseph et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…These multi-race or multi-biotype resistant genotypes proved to be more durable than any single-race or single-biotype resistance. Several researchers have reported the successful application of MAS in rice for targeted improvement of varieties and hybrid rice parental lines (Sundaram et al, 2009;Basavaraj et al, 2010;Rajpurohit et al, 2010;Hari et al, 2011;2013;Khanna et al, 2015;Ellur et al, 2015;Pradhan et al, 2015 andBhaskar et al, 2015).…”
Section: Yield and Agronomic Performance Of Improved Parental Linesmentioning
confidence: 99%